The Effect of the Thermal Frequency Device for Shock Waves on the Efficiency of the Knee Joint and the Skill of Rotating The Cord Backward by Bounce for Female Students with Simple Rupture of the Lateral Collateral Ligament - Rehab Nabeel Abd Alazem; Ammar Hamza Hadi; Mayson Hussien Alwan (Indian Journal of Forensic Medicine & Toxicology, 2021)
The research problem lies in the injury of the collateral ligament of the knee joint and what causes this injuryof pain. This pain increases in cases of bending and extending the knee joint for any movement and byinforming researchers about the physical therapy units, they found that rehabilitation of the injury is usuallythrough traditional rehabilitative exercises, such as weights, for example, which are often unwanted by theinjured who prefer the faster and easier method of performance and by using modern devices, including thethermal frequency device and the shock waves because it generates the desire and the rehabilitation andpsychological effect on the injured, therefore, the researchers decided to go into this experiment by usingrehabilitative exercises in a scientifically studied manner accompanied by a thermal frequency device andvibrational waves to rehabilitate the collateral ligament injury for students by strengthening the musclessurrounding the joint, in addition, the development of some rope skills in rhythmic gymnastics for students,and the research aims to prepare rehabilitative exercises accompanied by a thermal frequency device forvibrational waves in the efficiency of the knee joint and the skill of rotating the rope backward with reboundfor students with a simple tear of the lateral ligament, the researchers used the experimental approach inthe method of (one group) with the two pre and post-tests due to its suitability to the nature of the problem,the sample was chosen by the intentional method of (7) students with partial tearing of the lateral ligamentof the knee joint based on a medical report from the specialist doctor, and after a medical examination andan (MRI) scan. In light of the results reached by the researchers, the following conclusions came out: Therehabilitative exercises have a positive effect in rehabilitating the partial tear of the lateral ligament forstudents with rhythmic gymnastics.